Social polarization and its effect on the formation and growth of radicalism in Syria Emphasizing the ethnic gaps – religious - یدالله دهقان; محمود کتابی; مسعود جعفری نژاد (Faṣlnāmah-i Pizhūhish/hā-yi Rāhburdī-i Siyāsat, 2017)
Since the beginning of the Syrian crisis in 2011, many analysts consider this crisis to be result of a conspiracy from outside actors mainly US and Britain and their regional allies such as Israel and Saudi Arabia. But some internal social gaps Such as ethnic and religious gaps mainly Shiite - Sunni and outgroup Kurdish - Arabic conflicts had led to the outbreak of a civil war in this country. In this paper, the main question is: how does the social gaps, mainly ethnic and religious, affect the formation and growth of radicalism in this country? It is argued that there are two major ethnic and religious gap in Syria and due to inability of the government in managing these gaps and extensive foreign involvement, Syria has faced conflict and social unrest. Therefore, from the beginning of the crisis in 2011 and with the massive influx of foreign militants into the country, Religious Ethnic gaps have also been extremely deepened and led to the growth of radical groups.